Anatomy of Hematopoiesis and Local Microenvironments in the Bone Marrow. Where to? - Wu, Qingqing; Zhang, Jizhou; Lucas, Daniel (Frontiers in Immunology, 2021)
The shape and spatial organization -the anatomy- of a tissue profoundly influences its function. Knowledge of the anatomical relationships between parent and daughter cells is necessary to understand differentiation and how the crosstalk between the different cells in the tissue leads to physiological maintenance and pathological perturbations. Blood cell production takes place in the bone marrow through the progressive differentiation of stem cells and progenitors. These are maintained and regulated by a heterogeneous microenvironment composed of stromal and hematopoietic cells. While hematopoiesis has been studied in extraordinary detail through functional and multiomics approaches, much less is known about the spatial organization of blood production and how local cues from the microenvironment influence this anatomy. Here, we discuss the studies that revealed a complex anatomy of hematopoiesis where discrete local microenvironments spatially organize and regulate specific subsets of hematopoietic stem cells and/or progenitors. We focus on the open questions in the field and discuss how new tools and technological advances are poised to transform our understanding of the anatomy of hematopoiesis.